(untitled) (Ornitología Colombiana, 2021)
The Yellow-billed Cacique (Amblycercus holosericeus) belongs to a monotypic icterid genus distributed through most of Central and South America. It builds an open-cup nest, which distinguishes it from the nesting of other caciques. Little has been published on its breeding biology outside of Costa Rica. We provide the first observations on its nesting and incubation behavior from a nest studied in northeastern Ecuador. The nest was an open cup of vine tendrils and Chusquea bamboo leaves, built 2.6 m above the ground in a dense stand of bamboo. The two eggs were incubated for 64.1% of the observation period, made during the final nine days of incubation. Mean duration of on bouts was 40.7 min and mean off bout duration was 24.4 min. The incubating adult frequently slept on the nest by tucking its head under its wing, and often used the typical icterid foraging maneuver of slightly opening its bill to probe into the nest. The nest and eggs described here from Ecuador are very similar to descriptions from other parts of the species’s range. This record suggests that the Yellow-billed Cacique nests during the drier season, like other bamboo specialists breeding in our study area.